RANCANGAN SCREENING STRES KERJA DENGAN METODE FORWARD CHAINING BERBASIS ANDROID - Levina; Sigit Birowo (Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
In this age of globalization, technology is developing drastically and globally. Technological advances in various fields have been used by humans to make work fast and efficient. This research was motivated by the problem of the lack of public knowledge about work stress, the difficulty of screening on oneself without meeting experts, and not having received an application for job stress screening. Researcher uses the theories of data, systems, and information systems. Researcher also writes information about screening and job stress. This research is developed using Android Studio as a tool and using the Java language to develop this application. Researchers applied the Forward Chaining method in determining the results of job stress screening. Informastion gathering was done by field study, direct observation and interviews with child and adolescent psychiatrist, Dr. dr. Surilena, SpKJ(K)., and literature study such as reading books, journals and website as supporting reference for this research. This application was made to carry out job stress screening based on knowledge from experts to detect the risk and help in conducting consultations between users and experts. Through step by step research and program development, researcher concludes that the application that researcher made can determine symptoms of job stress risk based on expert konwledges and conduct consultation between users and experts. Key words : Forward chaining, Screening, Job Stress, Android